Environmental Vulnerability of the Buriticupu River Water Basin, Maranhão - Brazil: The Relief as a Key Element - Medeiros, Rafael Brugnolli; Santos, Luiz Carlos; Bezerra, José Fernando Rodrigues; Silva, Quesia Duarte; Melo, Silas Nogueira (Sociedade & Natureza, 2023)
Studying a watershed in the Amazon region requires understanding that this region has national and global relevance. The fact that the study area is located in the so-called arc of deforestation raises the need to understand its context, its vulnerabilities, and its physical, environmental, and anthropic components. This research assesses the environmental vulnerability of the Buriticupu River Watershed in Maranhão State, Brazil. The aim is to foster improvements that may contribute to environmental planning and, specifically, to water resource management. For this purpose, the authors used the Geographic Information System environment to work with Map Algebra, interrelating primary and secondary data on geology, relief, pedology, and land use and land cover to generate synthesis cartography. The results pointed to areas with predominantly medium vulnerability. However, the analyses highlight alluvial plains, which became the most fragile areas from an environmental point of view. This is mainly because these areas comprise water-saturated soils (gleysols), unconsolidated deposits of sand and silt (alluvial deposits), and extensive humid vegetation, characteristics of igapó and floodplain forests. This research generated a document that applies is applicable to the study area. It also provided, in a systemic and integrated way, a product that will help in planning, which is very important for the creation of a watershed committee, something necessary and still embryonic in Maranhão State, Brazil.